Zinc Ion-Stabilized Aptamer-Targeted Black Phosphorus Nanosheets for Enhanced Photothermal/Chemotherapy Against Prostate Cancer - Gao, Li; Teng, Ruobing; Zhang, Sen; Zhou, Yun; Luo, Miaomiao; Fang, Youqiang; Lei, Lei; Ge, Bo (Frontiers in Bioengineering and Biotechnology, 2020)
Prostate cancer is the second most common malignancy among men worldwide. However, conventional chemotherapy, such as taxane therapy, fails to exhibit efficient treatment for almost half of the patients. In this study, a nano-drug delivery system based on black phosphorus nanosheets (BP NSs) was developed, which was then employed as a multifunctional nanoplatform for targeted combinational chemo-photothermal therapy against prostate cancer. Zinc ion (Zn2+), which has been proven to be able to inhibit prostate cancer cell proliferation, was also introduced into this system. Zn2+ coordination could not only enhance the therapeutic effect of combined chemo-photothermal therapy, but also improve the intrinsic instability of BP NSs through the stabilization of its lone pair electrons. The in vivo study showed the outstanding performance of this system in targeted photothermal/chemotherapy of prostate cancer without side effect to normal organs.